The Principal's Performance as a Supervisor in Improving the Professionalism of Teachers - Nina Mardiana; Fatiah Khairani; Lis Khotimah; Riri Raudhotul Jannah; Irnie Victorynie (Civiliza Publishing, Indonesia., 2026)
The principal holds a strategic role as a supervisor who is responsible for guiding and developing teacher professionalism so that the quality of the learning process continuously improves. This study aims to describe the principal's role as a supervisor in fostering teacher professionalism, to identify the stages of academic supervision, and to reveal the obstacles faced by the principal in carrying out the supervisory function at TK Islam Terpadu Adam School. This study employed a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews with one principal and two teachers as informants, then analyzed through data reduction, data display, and conclusion drawing. The results show that the principal performs the supervisory role through strengthening teachers' academic competence, building teacher learning communities, conducting in-house training, modeling exemplary practice, and technology-based monitoring through closed circuit television (CCTV) and daily digital reporting. Supervision is carried out periodically through planning, classroom observation, joint evaluation and reflection, and follow-up in the form of feedback and teacher development programs. The obstacles found include the principal's limited time due to concurrent duties and weak completeness of teachers' instructional administration. These obstacles are addressed through delegation, strengthened communication via online groups, and cultivating a culture of joint reflection. This study recommends strengthening a technology-based supervision system combined with a humanistic approach so that the coaching of teacher professionalism can run sustainably.